MEANS OF CREATING A SATIRICAL AND HUMOROUS EFFECT IN POLITICAL DISCOURSE - Fahriddinova Nodira Fahriddinovna (TADQIQOTLAR.UZ, 2024)
Abstract: This article delves into the study of literary means which help creating a satirical and humorous effect in political discourse. By analyzing comedy shows, cartoons, social media in politics, this research offers nuanced insights into satire and humor and provide examples of irony, wordplay and pun, exaggeration.